2014
DOI: 10.1007/s00467-014-2798-3
|View full text |Cite
|
Sign up to set email alerts
|

Unwrapping the origins and roles of the renal endothelium

Abstract: The renal vasculature, like all vessels, is lined by simple squamous epithelium, called an endothelium. These endothelial-lined vessels can be subdivided into four major compartments: arteries, veins, capillaries and lymphatics. The renal vasculature is a highly integrated network that forms through the active processes of angiogenesis and vasculogenesis. The precise contribution of these two processes and the molecular signaling that governs the differentiation, specification and maturation of these critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 69 publications
1
27
0
Order By: Relevance
“…Recent studies have suggested that VEGF and VEGF-eNOS axis bioavailability decreased progressively in stenotic kidneys. Administration of VEGF can induce renal angiogenesis and alleviate renal fibrosis, and therefore VEGF therapy could provide a novel clinical approach in the treatment of chronic kidney disease (He et al, 2013;Stolz et al, 2015). By immunohistochemistry, expressions of VEGF and VEGFR2 were found to decrease in obstructed kidney of unilateral ureteral obstruction mice, and shenkang injection was found to increase expressions of VEGF/ VEGFR2 in this study.…”
Section: Discussionsupporting
confidence: 53%
“…Recent studies have suggested that VEGF and VEGF-eNOS axis bioavailability decreased progressively in stenotic kidneys. Administration of VEGF can induce renal angiogenesis and alleviate renal fibrosis, and therefore VEGF therapy could provide a novel clinical approach in the treatment of chronic kidney disease (He et al, 2013;Stolz et al, 2015). By immunohistochemistry, expressions of VEGF and VEGFR2 were found to decrease in obstructed kidney of unilateral ureteral obstruction mice, and shenkang injection was found to increase expressions of VEGF/ VEGFR2 in this study.…”
Section: Discussionsupporting
confidence: 53%
“…The blood that is filtered exits via the efferent arterioles that are juxtaposed to the afferent arterioles. We could visualize these arterioles with their brightly stained borders, as these arterioles have an actin filament‐rich smooth muscle lining (their locations are marked as ‘A’ in Fig. C).…”
Section: Resultsmentioning
confidence: 99%
“…The renal vasculature is formed by both angiogenesis (vessel sprouting from an existing vessel) and vasculogenesis (new vessel formation from EPCs) [52]. In adulthood, EPCs have been described to reside in the bone marrow, circulating blood, and blood vessels, whereas incompetence of resident EPCs has been reported in human CKD and several kidney injury models [33].…”
Section: Angiogenesis-based Treatment Of Kidney Diseasementioning
confidence: 99%